2022
DOI: 10.7759/cureus.26433
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Flexion Type Supracondylar Humeral Fracture With Ulnar Nerve Injury - A Report of a Rare Case

Abstract: Supracondylar humerus fractures in children account for up to two-thirds of pediatric elbow injuries that require hospitalization. Supra-condylar fractures usually occur due to falls from height, from sports, or through acts of leisure. The estimation of their incidence is about 177.3 per 100000. Here, we report a successfully managed case of flexion-type supra-condylar fracture of the humerus with ulnar nerve injury without any complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Kuoppala et al reported that seven patients with flexion-type SHFs showed increased carrying angles (CA): the mean CA was 50% greater in injured elbows (21°) than in uninjured elbows (14°) [ 9 ]. Moreover, case reports by Hara et al [ 10 ] and Vellingiri et al [ 11 ] on the surgical treatment of flexion-type SHFs demonstrated an increased CA in all three patients at the final follow-up. In our case, the patient showed an increase in the HEW angle by 14°, and radiographic images revealed the presence of subtle comminution of the lateral column.…”
Section: Discussionmentioning
confidence: 74%
“…Kuoppala et al reported that seven patients with flexion-type SHFs showed increased carrying angles (CA): the mean CA was 50% greater in injured elbows (21°) than in uninjured elbows (14°) [ 9 ]. Moreover, case reports by Hara et al [ 10 ] and Vellingiri et al [ 11 ] on the surgical treatment of flexion-type SHFs demonstrated an increased CA in all three patients at the final follow-up. In our case, the patient showed an increase in the HEW angle by 14°, and radiographic images revealed the presence of subtle comminution of the lateral column.…”
Section: Discussionmentioning
confidence: 74%